2002
DOI: 10.1074/jbc.m108417200
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 Interacts with Many Apparently Unrelated Proteins by Recognizing Short Amino Acid Sequences

Abstract: The chromatin high mobility group protein 1 (HMGB1) is a very abundant and conserved protein that is structured into two HMG box domains plus a highly acidic C-terminal domain. From the ability to bind DNA nonspecifically and to interact with various proteins, several functions in DNA-related processes have been assigned to HMGB1. Nevertheless, its functional role remains the subject of controversy. Using a phage display approach we have shown that HMGB1 can recognize several peptide motifs. A computer search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 51 publications
3
78
2
Order By: Relevance
“…These results show that HMGB1 itself has only minimal proinflammatory properties, but it acquires much greater activity through its role as a carrier protein for cytokines or other mediators capable of inducing cell activation. HMGB1 has previously been shown to bind in the intracellular milieu to a wide range of proteins, including transcriptional factors, steroid receptors, and viral proteins (34). The present findings, as well as those of other laboratories (16,17), demonstrate that extracellular proteins, such as cytokines and DNA-containing immune complexes, can also bind to HMGB1, creating a proinflammatory complex.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…These results show that HMGB1 itself has only minimal proinflammatory properties, but it acquires much greater activity through its role as a carrier protein for cytokines or other mediators capable of inducing cell activation. HMGB1 has previously been shown to bind in the intracellular milieu to a wide range of proteins, including transcriptional factors, steroid receptors, and viral proteins (34). The present findings, as well as those of other laboratories (16,17), demonstrate that extracellular proteins, such as cytokines and DNA-containing immune complexes, can also bind to HMGB1, creating a proinflammatory complex.…”
Section: Discussionsupporting
confidence: 59%
“…The present findings, as well as those of other laboratories (16,17), demonstrate that extracellular proteins, such as cytokines and DNA-containing immune complexes, can also bind to HMGB1, creating a proinflammatory complex. Although the sites for interaction between HMGB1 and IL-1␤ were not examined in these experiments, previous studies have shown that the A and B boxes, and possibly the highly acidic C terminal domain, are involved in HMGB1 binding to proteins (34).…”
Section: Discussionmentioning
confidence: 99%
“…Because distinct sets of ligands have been shown to interact with TLR2 and TLR4, it is likely that different regions of HMGB1 may be responsible for the associations observed in the present experiments with each of these receptors. HMGB1 has been shown to interact with a wide range of proteins, including transcriptional factors (21,47), steroid receptors (3,28), and viral components (7), through its A and B box domains, and possibly through the highly acidic COOH-terminal domain (10). With a phage display approach, HMGB1 was shown to recognize more than 12 different peptide sequences, indicating that HMGB1 is capable of associating with multiple proteins (10).…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 has been shown to interact with a wide range of proteins, including transcriptional factors (21,47), steroid receptors (3,28), and viral components (7), through its A and B box domains, and possibly through the highly acidic COOH-terminal domain (10). With a phage display approach, HMGB1 was shown to recognize more than 12 different peptide sequences, indicating that HMGB1 is capable of associating with multiple proteins (10). In those studies, different peptide sequences were found to associate with either the A or B box of HMGB1, suggesting that HMGB1 does not have a restricted interaction sequence.…”
Section: Discussionmentioning
confidence: 99%
“…As noted, HMGB1 has a unique regional structure in which different sequences allow interaction with biochemically disparate molecules (33). This property suggests that extracellular HMGB1 could be less discreet in its interaction with receptors in comparison to a conventional cytokine.…”
Section: Effects Of Redox On the Immune Activity Of Hmgb1mentioning
confidence: 99%